Chronic Energy Deficiency of Mothers as a Dominant Factor to Stunting in Toddlers of Smallholder Oil Palm Farmer Households in Muaro Jambi Regency, Jambi Province, Indonesia - Kalsum, Ummi; Guspianto, Guspianto; Monalisa, Monalisa; Diastanti, Yunita; Alamsyah, Zulkifli; Qaim, Matim (Program Studi Ilmu Kesehatan Masyarakat, Universitas Jambi, 2025)
The aim was to analyze the relationship between maternal health, nutritional status, and feeding practices for toddlers and the incidence of stunting in oil palm farmer households. This study design was cross-sectional. The samples were mothers and toddlers from oil palm farmer households who were randomly selected, as many as 227 from 8 villages in Muaro Jambi Regency. Collecting data by interview and anthropometric measurements. Stunting was measured using Height/Age < -2 Standard Deviation. Data analysis used Chi-square and multiple logistic regression. The incidence of stunting was 30.4%. Maternal nutritional status was 4.8% thin, overweight was 48.9%, and Chronic Energy Deficiency (CED) was 8.4%. Poor feeding patterns for toddlers 38.3%. The morbidity of mothers with infectious diseases was 10.1%. The dominant factor of stunting in toddlers in oil palm farmer households was the CED of mothers (POR = 2.34; 95% Confidence Interval = 0.78-7.00) after being controlled by maternal nutritional status, feeding patterns, and food insecurity. It is recommended to apply a healthy lifestyle, have a balanced and diverse nutritional diet for the mother, and pay good attention to her feeding practice for children. Improving nutrition and health education is very necessary for mothers. Keywords: Stunting, CED, toddlers, oil palm, smallholder